When mobile phone use becomes problematic : the influence of self, parents and peers on adolescents' mobile phone behavior in Singapore and Malaysia - Chuah, Soo Fei (2018)
As mobile phones become prevalent in our daily lives, studies have been conducted to investigate the reasons behind the popularity of mobile phones. Mobile phones ease the communication between humans by overcoming geographical and time constraints. However, uncontrollable mobile phone usage could lead to negative consequences. Drawing on group socialization theory, this study investigates the factors affecting both mobile phone use and problematic mobile phone use among adolescents in Singapore and Malaysia. In particular, using survey questionnaire method, this study examines mobile phone use and problematic mobile phone use among adolescents by focusing on the three important agents of change in adolescents’ life – the self, parents, and peers. This dissertation comprises three parts. Using samples from Singapore and Malaysia, the first part of this dissertation validates the measurement of parental mediation and parenting styles. The second and third parts of this dissertation investigate the effects of adolescents’ personalities (such as self-esteem, extraversion, neuroticism, and self-control), parental influence (such as parental mobile phone use, parenting styles, and parental mediation), and peer influence (such as peer mediation, peer norms, and peer capital) on both mobile phone use and problematic mobile phone use among adolescents in Singapore and Malaysia. In addition, this study also compares the intensity of mobile phone use and problematic mobile phone use among adolescents in both countries. The results show that personalities, parents, and peers exerted considerable influence on Singaporean and Malaysian adolescents’ mobile phone use. Specifically, peer influence accounted for the largest amount of variance in predicting adolescents’ mobile phone use, followed by personalities and parental influence. This study found that extroverted Singaporean and Malaysian adolescents are more likely to use mobile phones. In addition, the results show that peer discussion of mobile phone, injunctive norms, and peer capital are significantly associated with adolescents’ mobile phone use in Singapore and Malaysia. In contrast, personalities accounted for the largest amount of variance in predicting problematic mobile phone use among adolescents in both countries. This study found that adolescents with higher neuroticism trait and lower levels of self-control are more likely to involve in problematic mobile phone use. Moreover, the findings show that authoritarian parenting, restrictive mediation, mobile monitoring, peer discussion, and injunctive norms are significantly associated with problematic mobile phone use. The results also reveal that Singaporean adolescents have a higher frequency of mobile phone use as compared to Malaysian adolescents, but Malaysian adolescents tend to experience problematic mobile phone use more than their Singapore counterparts. This study contributes to the growing literature of mobile phone use and problematic mobile phone use by supporting the Big Five Theory, parenting styles model, parental mediation theory, social norm theory, and the social capital theory. This study also provides practical recommendations for policymakers, educators, and parents to mitigate problematic mobile phone use among adolescents.